FISH deletion mapping defines a single location for the Y chromosome stature gene, GCY - Kirsch, Stefan; Weiß, Birgit; Rosa, M. De; Ogata, T.; Lombardi, G.; Rappold, Gudrun (Journal of medical genetics, 2000)
At least 1 in 1000 males lacks part of the long arm of the Y chromosome. This chromosomal aberration is often associated with short stature and infertility. Deletion mapping and genotype-phenotype analysis have previously defined two non-overlapping critical regions for growth controlling gene(s), GCY(s), on the euchromatic portion of the Y chromosome long arm. These initial mapping assignments were based on the analysis of patients carrying a pure 46,XYq− karyotype as defined by classical cytogenetic karyotyping. Four genes have been assigned to the distal one of the two critical regions. To determine whether one or both of these two critical regions harbours GCY and whether one of the four genes assigned to the distal region is involved in determination of stature, nine adult patients with Yq chromosomal abnormalities were studied in detail. By PCR and FISH analysis, we showed that all patients with a previously defined pure 46,XYq− karyotype are actually mosaics with cells containing an idic(Y) or ring(Y) chromosome in association with 45,X0 cells. This leads us to conclude that (1) FISH is an absolute prerequisite for the correct identification of Y chromosomal rearrangements and (2) only patients with interstitial Y deletions are reliable predictors for the physical location of stature gene(s) on Yq. Our molecular analyses of chromosomes from patients with interstitial Yq deletions finally establishes the proximal interval between markers DYZ3 and DYS11 as the only GCY critical interval. No functional gene has so far been identified in this region adjacent to the centromere.
Gesehen am 24.03.2021